Łowca w każdym z nas? - Wężowicz‑Ziółkowska, Dobrosława (Zoophilologica. Polish Journal of Animal Studies, 2018)
By proposing a thesis, which is consistent with the results of biological research in the human evolution, that due to the pressure of natural selection and the evolutionary history of Homo sapiens our species was equipped with a strong predatory instinct, which enables us to speak about “the hunter in each of us”, the author of the article traces its cultural expressions, demonstrating its realisations in the past. She proves that this instinct, in conjunction with the strategy of costly representation (the handicap theory) which is also peculiar to humankind, is currently realised inter alia by hunting practices, which due to their cruelty and the incompatibility with a classless society constitute a peculiar “relic of barbarity”.